Effectiveness of digital media-based health education in improving adolescent health literacy on the prevention of sexually transmitted diseases - Risna Ayu Rahmadani; Etty Komariah Sambas; Matilda Martha Paseno; Wibowo Wibowo; Fitriani Fitriani (Edukasi Ilmiah Indonesia, 2026)
Introduction: Sexually transmitted diseases (STDs) continue to pose significant health risks among adolescents, partly due to inadequate access to accurate health information and limited health literacy. Digital media has emerged as a promising platform for health promotion, yet evidence regarding its effectiveness in enhancing adolescent health literacy specifically related to STD prevention remains limited. This study aimed to evaluate the effectiveness of digital media-based health education in improving adolescent health literacy regarding the prevention of sexually transmitted diseases. Research Methodology: A quasi-experimental study employing a pretest–posttest control-group design was conducted among 142 adolescents aged 15–19 years recruited from selected senior high schools in Makassar, Indonesia. Participants were allocated into intervention (n = 71) and control (n = 71) groups. The intervention group received digital media-based health education through educational videos, infographics, and interactive online modules for four weeks, while the control group received conventional health education. Data were analyzed using descriptive statistics, paired and independent t-tests, chi-square tests, and multiple linear regression using SPSS version 29.0. Results: Health literacy scores in the intervention group increased significantly from 63.1 ± 8.2 to 82.7 ± 7.4 (p < 0.001), whereas the control group showed no significant improvement (62.4 ± 8.5 to 66.1 ± 8.3; p = 0.056). Post-intervention scores were significantly higher in the intervention group than in the control group (82.7 ± 7.4 vs. 66.1 ± 8.3; p < 0.001). A large intervention effect was observed (Cohen’s d = 1.91). Multiple linear regression identified digital media intervention as the strongest predictor of post-intervention health literacy (β = 0.503, p < 0.001), with the model explaining 49% of outcome variance (R² = 0.49). Conclusion: Digital media-based health education is highly effective in improving adolescent health literacy related to STD prevention. Integrating evidence-based digital health education into school and community health programs may strengthen preventive behaviors, expand access to reliable sexual health information, and support adolescent health promotion efforts.